Zigzag. - Lebensztejn, Jean-Claude (Paris : Flammarion, 1981)
Texte de Francis Bacon Maurice Blanchot Jorge Luis Borges Roger Caillois Jacques Cazotte Pierre Corneille John Donne J.C. Engelstein Sigmund Freud Baltasar Gracian Luther Henderson O. Henry Hokusai Hymne à Déméter Nestor Ibarra Franz Kafka Comte de Lautréamont Jean-Claude Lebensztejn Léonard de Vinci Lieou Hsiang Stéphane Mallarmé Octave Mannoni Suarez Miranda Gérard de Nerval Pausanias Pline l'Ancien Marcel Proust Frank Stella Vous Anonymes divers ; Musique de Wolfgang Amadeus Mozart
boek